The Importance of Hand Hygiene in Infection Prevention - Ahmad Saeed Assiri,; Ahmed Dehman Al Shehri,; Dhafer Ali Al Omar,; Naif Mohammed Al Amri,; Ibrahim Yahya Al Saeed,; Saeed Abdulmohssen Al Malki, (International Journal of Medical Toxicology and Legal Medicine, 2025)
Hand hygiene is widely regarded as one of the fundamental pillars of infection prevention, particularly in healthcare settings where patients are at risk of healthcare-associated infections (HAIs). This paper identifies ways in which hand hygiene is important as a method to reduce the transmission of pathogens, particularly during the COVID-19 pandemic. This study references global and regional literature to assess the current levels of knowledge, attitudes, practices, and compliance among healthcare workers, students, and the community. It also identifies behavioral, structural, and systemic influences on individual and group compliance and describes types of interventions, including education, training, and policy implementation options. The evidence suggests that being mindful of effective hand hygiene can significantly reduce rates of infection and increase patient safety. Despite this, there remain barriers to compliance, such as facility-related resource constraints, education and training, and institutional commitment to hand hygiene as an organizational action. This paper concludes by urging stronger and effectively tailored promotion and advocacy of hand hygiene supported by relevant behavioral research, and in appropriate settings in healthcare.